A brief history of the classification and nomenclature of Odonata* - Trueman, John W.h. (Zootaxa, 2007)
The classification of insect order Odonata is traced from Linnaeus’ Systema Naturae, through 19th and 20th century morphology-based taxonomies, to molecular phylogenies published before November, 2007. Past and present nomenclatural difficulties are reviewed and the current situation in regard to rival taxonomies is outlined. Ordinal classifications based on morphological data continue to suffer from intractable uncertainty concerning wing vein homologies between Odonata and other Pterygota, but molecular analyses may soon show where the phylogenetic tree of Odonata should be rooted. The natural classification will become much clearer once this has been achieved.